2018
DOI: 10.1051/e3sconf/20184006015
|View full text |Cite
|
Sign up to set email alerts
|

Velocity profile and depth-averaged to surface velocity in natural streams: A review over alarge sample of rivers

Abstract: For measuring flood discharge with non-intrusive methods, one should know the depth-averaged to surface velocity ratio α. In this paper, a large sample of gauging (3611 gaugings over 176 sites of EDF-DTG) realized with a current meter are analyzed to compute α with three methods: fitting of a log- and a power-law and using the measured surface velocity. Results show that the three methods give very similar results, with a mean value of α of about 0.8, with few dispersion (5th and 95th percentile values being a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 9 publications
2
58
0
5
Order By: Relevance
“…Particle image and tracking velocimetry has emerged as a method for measuring surface velocity and computing discharge from the ground [12][13][14], from small, unmanned aircraft systems (sUAS) [15][16][17], and from manned aircraft systems [18]. Satellite-based sensors can be used to derive parameters such as water elevation, slope, and top width.…”
Section: Introductionmentioning
confidence: 99%
“…Particle image and tracking velocimetry has emerged as a method for measuring surface velocity and computing discharge from the ground [12][13][14], from small, unmanned aircraft systems (sUAS) [15][16][17], and from manned aircraft systems [18]. Satellite-based sensors can be used to derive parameters such as water elevation, slope, and top width.…”
Section: Introductionmentioning
confidence: 99%
“…The exponent, notated 1/ m ′ , refers to the power model that describes the velocity profile v ( z ) at elevation z above the bed vfalse(zfalse)=vfalse(hfalse)()zh1false/m where v ( h ) is the velocity measured at elevation h . In rivers, the exponent can range from 1/3 to 1/10 (Hauet et al, ).…”
Section: Experiments and Methodsmentioning
confidence: 99%
“…where v(h) is the velocity measured at elevation h. In rivers, the exponent can range from 1/3 to 1/10 (Hauet et al, 2018).…”
Section: Quality Review Of Raw Discharge Measurements and Choice Of Ementioning
confidence: 99%
“…Hauet et al. (2018) observed values of 0.8 with narrow dispersion (5th and 95th percentile values being about 0.7 and 0.9). The authors found that the value of this coefficient increases linearly with hydraulic radius and suggested 0.8 with an uncertainty ±15% at 95% confidence interval for water depths smaller than 2 m. Thus, the uncertainty in this velocity coefficient can lead to uncertainty in discharge of more than 30%.…”
Section: Introductionmentioning
confidence: 96%